Two Roads Diverged: A Comparative Analysis of Indigenous Rights in a North American Constitutional Context - Vicaire, Peter (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2013)
Fuelled by contrasting political backdrops, indigenous tribes on opposite sides of what has become the Canadian-American border have travelled upon very different trajectories, receiving dissimilar treatment from the respective governments that have laid claim to their lands.Indian tribes in the United States have sometimes had progressive legislators and high-ranking government officials enact bold laws and policies that were instrumental in creating positive change. Inversely, Aboriginal peoples in Canada have generally had to muddle through decade after decade of middling, indifferent, or occasionally even malicious bureaucrats who have continued to be too sheepish or backward-thinking to make any significant improvements. Further, the Canadian Parliament has yet to offer any substantive legislation in the vein and magnitude of that which was vital in making positive changes for American Indian tribes, even though numerous independent sources have pointed to such an approach. Rather, decades of piecemeal legislation have served only as a half-hearted attempt to counter the more odious effects of the archaic Indian Act, while those laudable governmental voices that have called for bold, substantial change have been largely ignored.